2020
DOI: 10.3389/fmicb.2020.542372
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Geographical Transitions in Eukaryotic Phytoplankton Community Structure in the Atlantic and Pacific Oceans

Abstract: Dynamics of Uncultivated Predatory Phytoplankton multiple chloroplast genes as well as expression of a selfish element (group II intron) in the psaA gene. Comparative analyses across the Pacific and Atlantic sites support the conclusion that predatory dictyochophytes thrive under low nutrient conditions. The observations that several uncultured dictyochophyte lineages are seemingly capable of photosynthesis and predation, raises questions about potential shifts in phytoplankton trophic roles associated with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 102 publications
(216 reference statements)
0
76
2
Order By: Relevance
“…A dynamic ecological system underlies the annual cycle of phytoplankton biomass in the western North Atlantic. Phytoplankton composition has been observed to undergo major seasonal shifts (Choi et al, 2020;Kramer et al, 2020;Yang et al, 2020). Communities dominated by cyanobacteria, prasinophytes and pelagophytes in the early winter give way to a more diverse eukaryotic phytoplankton community in the spring.…”
Section: Introductionmentioning
confidence: 99%
“…A dynamic ecological system underlies the annual cycle of phytoplankton biomass in the western North Atlantic. Phytoplankton composition has been observed to undergo major seasonal shifts (Choi et al, 2020;Kramer et al, 2020;Yang et al, 2020). Communities dominated by cyanobacteria, prasinophytes and pelagophytes in the early winter give way to a more diverse eukaryotic phytoplankton community in the spring.…”
Section: Introductionmentioning
confidence: 99%
“…Among PPEs, Pelagomonas calceolata was the first described member of the heterokont class Pelagophyceae 19 . It has since been identified in many oceanic regions using its 18S rRNA sequence and chloroplastic genome [20][21][22] . Several studies have demonstrated the capacity of P. calceolata to adapt to different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Depth is the main axis of organization of both the heterotrophic and small photosyn- position depends strongly on depth and water mass (Treusch et al, 2009;Agogué et al, 2011;Choi et al, 2020). Notably, we observe that the samples from the three research cruises cluster together with differences attributable to water mass.…”
Section: Community Compositionmentioning
confidence: 66%
“…Incubations took place at 14 ∘ C in the dark in the temperature controlled room of the Pourquoi Pas?. ; Choi et al (2017Choi et al ( , 2020. PCR reactions contained 25 ng of template, 5 l of 10× buffer, 1 U of HiFi-Taq, 1.6 mM MgSO4 (Thermo Fisher) and 0.2 M of each primer.…”
Section: Respiration Ratementioning
confidence: 99%
See 1 more Smart Citation